Testing habitat suitability for shellfish restoration with small‐scale pilot experiments. Issue 2 (13th January 2023) - Benjamin, Emilee D.; Handley, Sean J.; Jeffs, Andrew; Olsen, Louis; Toone, Trevyn A.; Hillman, Jenny R.
Abstract: The global loss in ecosystem engineers has initiated calls for restoration, which includes the UN declaration of 2021–2030 as the decade of ecosystem restoration. As researchers dive into this decade it is important to consider the current state of an ecosystem to ensure restoration success. Pilot‐scale restoration has been recommended by global guidelines and standards as an effective starting point for restoration to provide valuable initial information to increase efficiency and success of subsequent larger‐scale restoration. To test habitat suitability, 4 t of green‐lipped mussels were placed onto three 2.25 m 2 plots at five locations with differing benthic environments and assessed over 2 years. This study had a mean of 85% mussel survival at four of the five locations, while the restored shellfish in one location were completely extirpated, most likely by sea star predation. This pilot‐scale restoration revealed location‐specific differences that have implications for ensuring larger‐scale restoration success, including mussel survival, density, and health, and recommends a timeframe of at least 18 months to properly assess habitat suitability. Overall, the results validated the efficacy of using small‐scale pilot experiments to test habitat suitability and optimize location selection to maximize success and efficiency of larger‐scale restoration efforts.